Evolution of caste in neotropical swarm-founding wasps (Hymenoptera : Vespidae; Epiponini) - Noll, F. B.; Wenzel, J. W.; Zucchi, R. (Amer Museum Natural History, 2004)
Reproductive castes are compared in species of swarming wasps representing all currently recognized genera of Epiponini (Polistinae). New morphometric data for nine measures of body parts and ovarian data are presented for 13 species. These are integrated with all similarly conducted available studies, giving a total of 30 species. Analysis reveals several syndromes relating reproductive and nonreproductive individuals: no meaningful distinction, physiological differences only, reproductives larger than nonreproductives with intermediate individuals present, reproductives different in shape from nonreproductives with no intermediates, and reproductives smaller in some aspects than nonreproductives. Distribution of these syndromes among species is consistent with phylogenetic relationships derived from other data. Optimizing these syndromes on the cladogram indicates that the basal condition of Epiponini is a casteless society that is not comparable to the primitively social genus Polistes where dominant queens control reproduction. Castes originate several times in Epiponini, with different results in different lineages. The best documented evolutionary sequence passes from casteless societies, to those with reproductives larger, to those with reproductives differing in shape from nonreproductives, to those with reproductives smaller in some measures. This sequence is consistent with Wheeler's theory of the origin of caste through developmental switches, and represents the most thorough test of that theory to date.